Wernicke's encephalopathy and alcohol-related disease. - Naidoo, D. P. (BMJ Group, 1991)
A pilot study of 31 consecutive alcohol-related deaths over an 8-month period revealed the presence of histologically diagnosed Wernicke's encephalopathy in 17 cases. Analysis of the clinical records revealed that a disturbance of the mental state was the commonest finding and neurological signs were present in only 2 of the 17 cases (ataxia 1, peripheral neuropathy 1). Analysis of 22 ward admissions for Wernicke's encephalopathy during the same 8-month period revealed that the diagnosis is easily made when neurological deficits (ophthalmoplegia, ataxia) accompany mental changes and when Wernicke's encephalopathy is the predominant illness. In patients with established alcohol-related disease attention is often directed to the presenting illness so that Wernicke's encephalopathy may easily be overlooked as a cause of deterioration in the mental state in these patients. It is recommended that routine management of patients with alcohol-related disease should include thiamine even if neurological signs are absent.